Synthesis and characterisation of metal ion-imprinted polymers for separation of selective rare earth elements - Nik Rohani, Nik Mustapa (2018)
Ion imprinted polymers (IIPs) have received much attention in diverse fields owing to their high selectivity for targeted metal ions. In the present study, lanthanide-ion imprinted polymers (L-IIPs) were synthesised by dissolving stoichiometric amounts of lanthanum ion and selected complexing agents either Schiff bases, azobenzene base ligands and also indole compounds with solvent in the presence of cross-linking agent (ethylene glycol dimethacrylate (EGDMA)), functional monomer (4-vinylpyridine), and initiator (2,2-azobisisobutyronitrile (AIBN)). The cavities in the polymer materials corresponding to the specific lanthanide ions were created by leaching the polymer using aqueous HCl solution after polymerization. The complete removal of the lanthanide ions from the L-IIPs were confirmed by ICP-MS, FESEM and solid state analysis by UV-vis NIR spectroscopy. FTIR study confirmed the complexation between the L-IIPs and lanthanide ions through the nitrogen, hydroxyl oxygen and sulphur of Schiff base, azobenzene base ligands and indole compounds. At optimum (pH 6), the maximum sorption capacity achieved by the L-IIPs are estimated to be La-IIP-Schiff (25.0 mg g-1), La-IIP-Azo (24.3 mg g-1), Ce-IIP-Schiff (24.5 mg g-1), Ce-IIP-Azo (24.7 mg g-1), Pr-IIP-Schiff (125.3 mg g-1), Nd-IIP-Schiff (126.5 mg g-1), Sm-IIP-Schiff (127.6 mg g-1), Eu-IIP-Schiff (128.2 mg g-1) and Gd-IIP-Schiff (129.1 mg g-1). In the selectivity study, the L-IIPs were found to show good selectivity to the praseodymium, gadolinium, europium, samarium, cerium, neodymium and lanthanum ion in the presence of coexisting cation, promethium. It was found that imprinting results increased the affinity of the material toward several lanthanide ions over other competitor metal ions with the same charge and similar ionic radii. The synthesized L-IIPs were repeatedly used and regenerated for 8 times without a significant decrease in polymer binding affinity.